The Measurement Model of Tourism Destination Images Using Fuzzy Inference System - I Nyoman Sutapa; Magdalena Wullur (Master of Management, School of Business and Management, Petra Christian University, 2018)
The article discusses the measurement model of tourism destination images perceived by travellers based on five dimensions of the service quality, i.e. tangibles, reliability, responsiveness, empathy, and assurance. Measurement problems occur when a traveller assesses the quality of a tourism destination service subjectively with vague boundaries and perceives the image of a tourism destination to vary. To address these issues, we designed an inference model using Mamdani's fuzzy inference system. The results of this study are quantitative assessments of the image of tourism destinations by various travellers based on qualitative perceptions of the quality of service experienced by the traveller.